2007
DOI: 10.1007/s10526-007-9104-2
|View full text |Cite
|
Sign up to set email alerts
|

Field persistence of the entomopathogenic nematode Heterorhabditis bacteriophora in different crops

Abstract: To investigate nematode establishment and persistence, dauer juveniles (DJs) of Heterorhabditis bacteriophora were applied at 50 cm -2 in different crops in June and July with conventional spraying equipment and 420 l water ha -1 . Application hardly had any effects on survival and infectivity. The number of DJs reaching the soil was assessed and the establishment and persistence recorded by baiting soil samples with larvae of the wax moth Galleria mellonella. The better the plant canopy was developed the fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 41 publications
3
70
0
Order By: Relevance
“…On the other hand, the large decline in the percentage of mortalities in the Block B vineyard between four and 12 weeks post-application may be due to the fact that, between these two periods, tillage had occurred between the grapevine rows. Work done by Entomopathogenic Nematodes to Control the Vine Mealybug Susurluk and Ehlers (2008) found that ploughing caused a decline in H. bacteriophora persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the large decline in the percentage of mortalities in the Block B vineyard between four and 12 weeks post-application may be due to the fact that, between these two periods, tillage had occurred between the grapevine rows. Work done by Entomopathogenic Nematodes to Control the Vine Mealybug Susurluk and Ehlers (2008) found that ploughing caused a decline in H. bacteriophora persistence.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a laboratory persistence trial for both H. zealandica and S. yirgalemense was conducted in the hope that comparable results could be produced for current and future studies. When investigating the persistence of nematodes in the field, results could possibly be influenced by the availability of insect hosts (Susurluk & Ehlers, 2008). Consequently, in-field persistence studies will not be able to distinguish between the persistence of the released population of EPNs and the continuation of offspring from the released population, otherwise known as recycling (Curran, 1993;Susurluk & Ehlers, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae) IJs reaching soil level immediately after spraying ranged from 5 to 6 % in dense canopy crops (oilseed rape and lupine) to 77-78 % in pasture and potatoes (Susurluk & Ehlers, 2008). As this was measured by placing Petri dishes on the soil it probably overestimates the numbers actually reaching the soil in a pasture with dense thatch, which can form a significant barrier to EPN dispersal (Zimmerman & Cranshaw, 1991).…”
Section: Fate Of the Inoculum: Death Or Dispersalmentioning
confidence: 99%
“…and help in developing the experimental set-ups. The fieldwork was possible thanks to the hospitality of the Plant Health Service in Hodmezovasarhely in Hungary, factors such as soil type, 23 humidity, 24 temperature 25 or pH. 24 But the main factor that is thought to determine long-term persistence in the field is the presence of available host insects.…”
Section: Diabrotica Virgifera Virgiferamentioning
confidence: 99%
“…24 But the main factor that is thought to determine long-term persistence in the field is the presence of available host insects. 25 In field trials in Hungary, three EPN species, H. bacteriophora, H. megidis and Steinernema feltiae, were released to test their control potential against WCR. They all persisted at least as long WCR were present in soil, during the same year.…”
Section: Diabrotica Virgifera Virgiferamentioning
confidence: 99%